Analisis Pola Hidup Sehat Dan Kebiasaan Bermain Gadget Pada Anak Kost Di Kota Medan - Amalia Paskah Sitorus; Imely Patricia K Banjarnahor; Mila Sari Butar -Butar; Erwita Ika Violina (CV. Eracita Grup, 2026)
This research seeks to study the patterns of healthy lifestyles and habits of gadget usage among boarding house students in Medan, while also exploring the connection between these aspects. The rising trend of gadget usage among college students residing in boarding houses has led to modifications in their daily routines, particularly in terms of eating practices, sleep cycles, and levels of physical activity. The methodology used in this study is descriptive quantitative, where data was gathered through questionnaires aimed at students aged 18-25 years in boarding houses. Subsequently, the collected data was analyzed using descriptive statistics to classify healthy lifestyle patterns along with the frequency of gadget usage. The outcomes reveal that a large proportion of boarding students exhibit less than optimal healthy lifestyle patterns, which can be observed through irregular eating habits, inadequate sleep, and minimal physical activity. Conversely, the average gadget usage among participants is notably high, exceeding 5 hours daily, primarily for social media engagement and entertainment. Further analysis indicates a negative correlation between the intensity of gadget usage and the manifestation of healthy lifestyle habits, illustrating that increased gadget use is linked to decreased sleep quality and lower physical activity. In summary, this study demonstrates that regular engagement with gadgets impacts the healthy lifestyle choices of students living in boarding houses in Medan. Thus, enhancing health literacy and managing gadget usage time effectively is crucial for fostering a more balanced lifestyle among these students.